ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PERUSAHAAN MELALUKAN PERGANTIAN KANTOR AKUNTAN PUBLIK ( STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2013-2014) - YANTI, MARTINA FAJAR; Halim, Abdul; Wulandari, Retno (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2016)
Substitution public accounting firm can be made mandatory and Voluntary in accordance with the focus of attention that occurs. If the change was involuntary, the primary focus is the company and vice versa. Many variables can affect the turn of the Public Accountant including management changes, Opinion Auditor, Financial Distress, Share Growth, and firm size. This study aims to examine and explain the effect of management changes, Opinion Auditor, Financial Distress, Share Growth, firm size, ROA and ROE Percentage tehadap Public Accounting Firm turnover of the company. The data used is data companies listed on the Stock Exchange in the period 2013-2014 which is accessed through the website of the Stock Exchange www.idx.co.id. Methods of data collection using purposive sampling method and sample obtained was 124 companies. Hypothesis testing is done using logistic regression analyzes with SPSS program. The results of this study indicate that a change of management, Auditor Opinion, Financial Distress, Share Growth, firm size, and ROE partially or jointly influence the turn of the KAP (Auditor Switching). ROA percentage is partially not yet jointly influence the turn of the KAP (Auditor Switching). The results showed Opinion Auditor influence the turn of KAP, which the company will choose the auditor who is willing to give opinions on the desired company. This is related to the independence of auditors and public accounting firm that is expected to further conduct research related research independence. The limited period of two years can certainly affect the results of this study. So hopefully in the next research study period should be more than two years to allow classification based audit tenure.